2016
DOI: 10.7748/ns.2016.e10292
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for delayed patient discharge following day surgery: a literature review

Abstract: NHS Trusts face considerable financial challenges. There is a drive to reduce costs by increasing day surgery rates, thereby reducing the length of post-operative stay. Some patients will not meet the discharge criteria to go home following day surgery, for a variety of reasons. They may then require an overnight stay in hospital, creating an unplanned cost. AimsThe aim of this article is to explore the reasons why some adult patients are not suitable for discharge following day surgery. MethodsA pragmatic, mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
(59 reference statements)
0
4
0
Order By: Relevance
“…One study investigating factors associated with early discharge of patients with GC undergoing gastrectomy found that several factors, such as improved PA, laboratory variables, minimally invasive surgery, and body temperature, could predict early discharge [43]. For the patients undergoing surgical procedures other than gastrectomy, the reports also supported the relationship between improved PA and early discharge [44,45]. Our study suggested that the surgical staff should regard PA as an important clinical parameter, which has previously been long ignored as research is often hindered by the challenge of adapting an easy, valid, and reliable measure to record PA [6].…”
Section: Discussionmentioning
confidence: 99%
“…One study investigating factors associated with early discharge of patients with GC undergoing gastrectomy found that several factors, such as improved PA, laboratory variables, minimally invasive surgery, and body temperature, could predict early discharge [43]. For the patients undergoing surgical procedures other than gastrectomy, the reports also supported the relationship between improved PA and early discharge [44,45]. Our study suggested that the surgical staff should regard PA as an important clinical parameter, which has previously been long ignored as research is often hindered by the challenge of adapting an easy, valid, and reliable measure to record PA [6].…”
Section: Discussionmentioning
confidence: 99%
“…Pain is a common reason for hospital readmission after surgery (Helgstrand et al 2011, Clement et al 2013, and may delay discharge following day care surgery (Rae 2016). Importantly, inadequate pain management after surgery can increase the risk of chronic postoperative pain (Joshi and Ogunnaike 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Effective postoperative pain management is a prerequisite of successful day surgery, and it is arguably the most challenging issue. Uncontrolled pain is typically one of the main reasons for delayed discharge in day surgery (Mitchell 2004, Rae 2016. Similarly, moderate to severe pain is commonly reported following discharge after day surgery (Elaqoul et al 2017) and previous studies have estimated that more than half of patients experience this level of pain in the first 24 hours of being home (Townsend & Cox 2007).…”
Section: Discussionmentioning
confidence: 99%